The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1093/jaoac/92.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Aucubin from Seeds of Eucommia ulmoides Oliv. Using Supercritical Carbon Dioxide

Abstract: Supercritical CO2 was used as solvent for the extraction of aucubin from the seeds of Eucommia ulmoides Oliv. The co-solvent composition was tested and extraction conditions were optimized. Results showed that the best co-solvent was a waterethanol mixture (1 + 3, v/v), and the highest yield was obtained when the extraction was performed under 26 MPa at extraction and separation temperatures of 55 and 30C for 120 min, using 6 mL co-solvent/g material at a CO2 flow rate of 20 L/h. In a comparison of the supercr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We found that E. ulmoides Oliver significantly regulated hepatic lipid accumulation both in vitro and in vivo . Our study results suggest that the regulatory mechanism of E. ulmoides Oliver and its active constituents, aucubin and geniposide [22] , [23] , toward hepatic dyslipidemia involves regulation of ER stress and associated lysosomal activity.…”
Section: Introductionmentioning
confidence: 65%
“…We found that E. ulmoides Oliver significantly regulated hepatic lipid accumulation both in vitro and in vivo . Our study results suggest that the regulatory mechanism of E. ulmoides Oliver and its active constituents, aucubin and geniposide [22] , [23] , toward hepatic dyslipidemia involves regulation of ER stress and associated lysosomal activity.…”
Section: Introductionmentioning
confidence: 65%
“…The palmitate-induced ROS accumulation was diminished by EUE or its active components, aucubin and geniposide ( Figure S3 ). Because the palmitate-induced cell death mechanism includes the lysosomal pathway and EUE regulates cell death through lysosomal activation [24] , we examined the effect of the active components, aucubin and geniposide, on lysosomal activation. First, lysosomal V-ATPase activity was analyzed through the acridine quenching method.…”
Section: Resultsmentioning
confidence: 99%
“…Aucubin is also a kind of iridoid compound, which is very unstable and sensitive to temperature. Therefore, longer heating process destructs the structure and decreases the content of aucubin (Li et al, 2009;Zheng et al, 2012). Table 1 reveals the lower aucubin content of all the processed samples than that of the control.…”
Section: Comparison Of Methodsmentioning
confidence: 99%